(untitled) (Papeles, 2021)
The study of social policies implemented at subnational level lets us account for complex issues which happen in urban territories and for the specificity of the answers developed to deal with those issues. This work firstly addresses the experience of Abre Plan in Santa Fe Province considering the previous conditions and context in which the actions are planned. Additionally, it presents the difficulties in continuity for the public policies which are not rooted in solid organic-functional structures when facing changes in government management. It also collects information about the networks and lessons that do remain amongst human resources which inhabit the State.